Academic and Commercial Circles in Block Chain Secure Privacy and Scalability at Block Chain Technologies - Kumari, Sony; Patil, Manoj Eknath (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In today's world, technological advancements and high-speed internet are indispensable in our daily lives, but these advancements come with their own set of challenges, especially in security. Blockchain technology, one of the most significant innovations in recent years, is gaining attention for its security applications across various sectors, including supply chain management and shipping. The education sector, particularly higher education institutions, is now exploring the use of blockchain to enhance teaching, learning, and collaboration among key stakeholders like students, teachers, and parents. Applications such as e-transcripts, digital degrees, certifications, cloud storage, and identity management stand to benefit from blockchain integration. This ongoing research delves into the potential application of blockchain in education, a topic that has recently garnered much interest across various industries. The study aims to provide a comprehensive overview of the current state of blockchain in education, which could inform future initiatives in this area. A thorough review of scholarly articles was undertaken, focusing exclusively on works that discuss blockchain in the context of education. Eleven different databases were meticulously searched to identify relevant publications, and 28 significant papers were selected for examination. To ensure objectivity and minimize biases in selection and analysis, three researchers were involved in the review process. Their analysis of the selected papers yielded crucial insights, addressing questions about the current application of blockchain in education, its beneficial features for the sector, and the challenges that need to be addressed for its wider adoption. This led to the development of several proofs of concept for blockchain in education. Blockchain can be widely implemented in the educational sector, several key challenges need to be addressed, including technical, legislative, and academic hurdles. Overcoming these challenges is essential for the successful integration and utilization of blockchain technology in educational settings.Top of Form